Penilaian Tingkat Kematangan Kualitas Data dalam Sistem Manajemen Aset: Studi Kasus dari Perusahaan Energi dan Utilitas , PT XYZ - Ramdhan Megantara, Mufqi (The Indonesian Journal of Computer Science, 2025)
Nowadays data assets have become critical for organizations, especially in asset-intensive industries like energy and utilities. PT XYZ, an energy, and utilities company in Indonesia, relies heavily on its assets and began transforming its asset management system using top-down approach in 2022. During this transformation, the organization faced significant challenges related to data quality. A maturity assessment based on David Loshin’s framework evaluated eight data quality domains and revealed an average maturity score of 2.06, indicating an initial-repeatable level with significant gaps in standards, technologies and performance management. These gaps hinder the achievement of strategic goals, including ISO 55001 certification. By integrating best practices from DMBOK and the Institute of Asset Management, a comprehensive recommendation was developed to address 31 identified gaps and elevate data quality maturity to defined level. Key recommendations include establishing robust governance, adopting advanced data quality technologies and implementing standardized policies, procedures and reporting to improve organizational performance.